2017
DOI: 10.1016/j.bbadis.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and mutations in the melanocortin-3 receptor and their relation to human obesity

Abstract: Inactivating mutations in the melanocortin 3 receptor (Mc3r) have been described as causing obesity in mice, but the physiologic effects of MC3R mutations in humans have been less clear. Here we review the MC3R polymorphisms and mutations identified in humans, and the in vitro, murine, and human cohort studies examining their putative effects. Some, but not all, studies suggest that the common human MC3R variant T6K+V81I, as well as several other rare, function-altering mutations, are associated with greater a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 86 publications
(146 reference statements)
0
29
0
Order By: Relevance
“…IKKα and IKKβ, the critical activators of the NF-κB pathway, are also involved in the regulation of β-catenin-dependent transcriptional activity 47 49 . Some studies support that calpain activity is required for wound healing, transgenic mice with overexpressed CAST, which displayed a striking delay in skin wound healing through impaired angiogenesis 13 , 50 . These differences imply that calpain-1/2 modulates angiogenesis via multiple mechanisms, depending on the environment and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…IKKα and IKKβ, the critical activators of the NF-κB pathway, are also involved in the regulation of β-catenin-dependent transcriptional activity 47 49 . Some studies support that calpain activity is required for wound healing, transgenic mice with overexpressed CAST, which displayed a striking delay in skin wound healing through impaired angiogenesis 13 , 50 . These differences imply that calpain-1/2 modulates angiogenesis via multiple mechanisms, depending on the environment and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the genes of each of the MCR subtypes have been identified in humans and other mammals, as summarized by Switonski et al [ 18 ]. MC1R is prominent in the synthesis of melanin in melanocytes, and mutations are associated with various skin phenotypes and diseases, including increased cancer risk, especially for melanomas [ 19 , 20 , 21 ]. Of interest, three reports indicate an association between disability in MS and MC1R gene single nucleotide polymorphisms leading to MC1R hyporesponsiveness [ 22 , 23 , 24 ].…”
Section: Melanocortin Receptorsmentioning
confidence: 99%
“…A mutation in the MC2R gene with increased expression and stronger response to ACTH has been associated with increased responsiveness to ACTH treatment of infantile spasms [ 25 , 26 ]. MC3R, like MC4R, is involved in energy homeostasis; while several human mutations have been identified [ 20 ], there is a less clear association with obesity for these mutations than for MC4R mutations. MC4R has been extensively investigated in obesity research, and decreased activity of MC4R is the leading monogenic cause of severe early onset obesity [ 27 , 28 ].…”
Section: Melanocortin Receptorsmentioning
confidence: 99%
“…However, mice lacking both MC3R and MC4R become significantly heavier than Mc4r−/− mice [ 42 ], indicating that they serve non-redundant roles in regulating energy homeostasis. No human MC3R mutations to date have been conclusively linked to severe obesity, even if multiple smaller studies have reported possible associations of MC3R variations with increased body weight [ 90 , 91 , 92 , 93 ], although nowhere near the effect size of that seen with mutations in MC4R. Taking into account all of the available evidence, MC3R is less likely to be related to food intake and more likely to revolve around nutrient partitioning.…”
Section: Genetics Of the Melanocortin Systemmentioning
confidence: 99%